RIPK3 Mediates Necroptosis during Embryonic Development and Postnatal Inflammation in Fadd-Deficient Mice - Qun Zhao (Cell Reports, 2017)
RIPK3 mediates cell death and regulates inflammatory responses. Although genetic studies have suggested that RIPK3-MLKL-mediated necroptosis leads to embryonic lethality in Fadd or Caspase-8-deficient mice, the exact mechanisms are not fully understood. Here, we generated Ripk3 mutant mice by altering the RIPK3 kinase domain (Ripk3Δ/Δ mice), thus abolishing its kinase activity. Ripk3Δ/Δ cells were resistant to necroptosis stimulation in vitro, and Ripk3Δ/Δ mice were protected from necroptotic diseases. Although the Ripk3Δ/Δ mutation rescued embryonic lethality in Fadd−/− embryos, Fadd−/− Ripk3Δ/Δ mice died within 1 day after birth due to massive inflammation. These results indicate that Ripk3 ablation rescues embryonic lethality in Fadd-deficient mice by suppressing two RIPK3-mediating processes: necroptosis during embryogenesis and inflammation during postnatal development in Fadd−/− mice.